Highlights in targeted nanoparticles as a delivery strategy for glioma treatment - Luiz, Marcela Tavares (2021)
Glioma is the most common type of Central Nervous System (CNS) neoplasia and it arises from glial cells. As glial cells are formed by different types of cells, glioma can be classified according to the cells that originate it or the malignancy grade. Glioblastoma multiforme is the most common and aggressive glioma. The high lethality of this tumor is related to the difficulty in performing surgical removal, chemotherapy, and radiotherapy in the CNS. To improve glioma treatment, a wide range of chemotherapeutics have been encapsulated in nanosystems to increase their ability to overcome the blood–brain barrier (BBB) and specifically reach the tumoral cells, reducing side effects and improving drug concentration in the tumor microenvironment. Several studies have investigated nanosystems covered with targeting ligands (e.g., proteins, peptides, aptamers, folate, and glucose) to increase the ability of drugs to cross the BBB and enhance their specificity to glioma through specific recognition by receptors on BBB and glioma cells. This review addresses the main targeting ligands used in nanosystems to overcome the BBB and promote the active targeting of drugs for glioma. Furthermore, the advantages of using these molecules in glioma treatment are discussed.